Meta-Analysis the Effect of Baby Massage in Increasing Quality of Sleep and Infant Body Weight - Fauzia, Raina Lola; Budihastuti, Uki Retno; Adriani, Rita Benya (Journal of Maternal and Child Health, 2022)
Background: Sleep patterns and weight in infants are identified as one of the most important topics related to infant growth and development. Baby massage is a slow and gentle stroke movement throughout the baby's body starting from the baby's feet, stomach, chest, face, hands and back. Baby massage is a form of touch stimulation. Babies who are massaged experience an increase in vagus nerve tone (10th brain nerve) which will lead to increased levels of gastrin and insulin absorption enzymes. Thus the absorption of food will be better. Therefore, body weight and sleep quality increased more than those who were not massaged. Subjects and Method: This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: PubMed, Science Direct, Google Schoolar and SpingerLink by selecting articles published in 2010-2020. The keywords used were (“baby massage” OR “infant massage”) AND (“sleep quality” OR “baby sleep quality”) AND (“weight gain” OR “baby weight gain”) AND “randomized controlled trial”. Inclusion criteria were full paper articles with Randomized Controlled Trial (RCT) research methods, the relationship measure used was Mean SD, the intervention given was baby massage, research subjects were infants aged 0-3 years. Eligible articles were analyzed using the Revman 5.3 application. Results: A meta-analysis of 16 articles showed that baby massage improved sleep quality (SMD 0.70; 95% CI= -0.05 to 1.46; p=0.07). In addition, baby massage increased body weight (SMD 0.52; 95% CI= 0.08 to 0.96; p=0.02). Conclusion: Baby Massage has an effect on improving the quality of sleep and baby's weight.